PENDEKATAN PARIWISATA BERBASIS MASYARAKAT / COMMUNITY BASED TOURISM (CBT) DI DESA WISATA LUMAJANG, KABUPATEN BANDUNG - Asyifa, Nurul; Pratama, Ricky Karya; Andjanie, Isabella Fitria; Furqan, Alhilal (Jurnal Master Pariwisata (JUMPA); Volume 10, Nomor 01, Juli 2023DO - 10.24843/JUMPA.2023.v10.i01.p09, 2023)
One of the challenges in realizing community-based tourism villages is the lack of experience among local communities in the development and management of tourism activities. Therefore, a comprehensive approach based on Community-Based Tourism (CBT) is needed. Lamajang Tourism Village, known for its cultural tourism potential, is currently developing its natural tourism. This research aims to assess and evaluate the readiness of community participation in managing tourism potential to become a quality, attractive, and sustainable tourism product. The research method used in this study is a descriptive qualitative approach. Data collection techniques involve field observations, interviews with various tourism stakeholders and local community figures, as well as analysis of policy documents from the local government of Bandung Regency. The assessment framework and indicators used in this study are based on the "Handbook on Community-Based Tourism: How to Develop and Sustain CBT". This research generates several conclusions and recommendations, including the need for evaluation and optimization at various stages of the CBT approach to advance Lamajang village, which is still considered an emerging tourism village, towards a developing/prospering tourism village. Keywords: community based tourism; indigenous village cikodang; Lamajang Village; tourism village.